Comparison of core full text coverage in CINAHL Complete, ProQuest's Nursing and Allied Health Source and Lippincott Wilkins and Wilson's Nursing & Health Professionals Premier Collection. Issue 1 (19th January 2015) - McGowan, Beth; Ayers, Meredith
Abstract : Purpose: – This paper aims to assess relative full-text coverage of core nursing and allied health journals in three databases: CINAHL Complete, ProQuest Nursing and Allied Health Source and Lippincott Wilkins and Wilson (LWW)'s Nursing & Health Professionals Premier Collection. Design/methodology/approach: – The 2012 Nursing and Allied Health Resources Section (NAHRS) of the MLA list of 213 core nursing journals and the 1996 Brandon Hill list of 75 important allied journals were checked against full-text coverage of the three databases. Findings: – CINAHL Complete provided 126 of 213 titles or 59 per cent of NAHRS titles and 31 of 75 or 41 per cent of the Brandon Hill titles; ProQuest provided 74 of 213 titles or 35 per cent of NAHRS titles and 27 of 75 or 36 per cent of the Brandon Hill titles; LWW provided 42 of 213 or 20 per cent of NAHRS titles and 5 of 75 or 6 per cent of the Brandon Hill titles. Research limitations/implications: – If researchers have access to CINAHL Complete, they have access with that single database to significant coverage of quality nursing and allied health titles. The other two databases provide additional coverage and some unique title coverage, but their offerings are more limited. Originality/value: – As no studies comparing full-text coverage of core nursing and allied health journals in three databases, CINAHL Complete, ProQuest Nursing and Allied Health Source and LWW's Nursing & Health Professionals Premier Collection, exist, this study fills that need for librarians.